2022
DOI: 10.31234/osf.io/8gmw3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infants expect friends, but not rivals, to be happy for each other when they succeed

Abstract: Emotions arise not just from people’s own circumstances, but also from the experiences of friends and rivals. Here we asked if human infants have expectations about vicarious emotions, and if they expect those emotions to be guided by social relationships. Ten- and 11-month-old infants (N=154) expected an observer to be happy rather than sad when the observer watched a friend successfully jump over a wall. In contrast, infants did not expect the observer to be happy when the friend failed, nor when a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Infants discriminate positive and negative facial expressions towards the end of their second year of life 45 . Likewise, previous studies demonstrated that actions of moving towards each other 13 as well as facial expressions 46 are also differentiated by infants (and elicit meaningful effects on measures of pupil dilation 25 ) for geometrically shaped characters. In addition, while former studies used explicit verbal expressions of praise and admonishment 47 here we created novel sounds to support the characters approval or disapproval.…”
Section: Methodsmentioning
confidence: 64%
“…Infants discriminate positive and negative facial expressions towards the end of their second year of life 45 . Likewise, previous studies demonstrated that actions of moving towards each other 13 as well as facial expressions 46 are also differentiated by infants (and elicit meaningful effects on measures of pupil dilation 25 ) for geometrically shaped characters. In addition, while former studies used explicit verbal expressions of praise and admonishment 47 here we created novel sounds to support the characters approval or disapproval.…”
Section: Methodsmentioning
confidence: 64%
“…Rivals hinder our access to resources, including partners and status (Buss et al, 2000;Duntley & Buss, 2011;Hilbe et al, 2018). Correspondingly, people's attitudes toward others appear to match the probable effects that others will have on their welfare: People value and like those who have a stake in their welfare or that of their kin (Lewis et al, 2015;Smith-Flores et al, 2024;Sznycer et al, 2019); people disvalue and dislike competitors, rivals, and enemies (Adams, 2005;Holt, 1989;Wiseman & Duck, 1995). But people's dyadic interactions with their associates-friends, spouses, rivals-do not take place in a social vacuum.…”
Section: A Theory Of Welfare Effectsmentioning
confidence: 99%